Development and characterization of silica and titania based nanostructured materials for the removal of indoor and outdoor air pollutants - Peiris, Thelge Manindu Nirasha (Kansas State University, 2012)
Solar energy driven catalytic systems have gained popularity in environmental remediation recently. Various photocatalytic systems have been reported in this regard and most of the photocatalysts are based on well-known semiconducting material, Titanium Dioxide, while some are based on other materials such as Silicon Dioxide and various Zeolites. However, in titania based photocatalysts, titania is actively involved in the catalytic mechanism by absorbing light and generating exitons. Because of this vast popularity of titania in the field of photocatalysis it is believed that photocatalysis mainly occurs via non-localized mechanisms and semiconductors are extremely important. Even though it is still rare, photocatalysis could be localized and possible without use of a semiconductor as well. Thus, to support localized photocatalytic systems, and to compare the activity to titania based systems, degradation of organic air pollutants by nanostructured silica, titania and mixed silica titania systems were studied. New materials were prepared using two different approaches, precipitation technique (xerogel) and aerogel preparation technique. The prepared xerogel samples were doped with both metal (silver) and non-metals (carbon and sulfur) and aerogel samples were loaded with Chromium, Cobalt and Vanadium separately, in order to achieve visible light photocatalytic activity. Characterization studies of the materials were carried out using Nova BET analysis, DR UV-vis spectrometry, powder X-ray diffraction, X-ray photoelectron Spectroscopy, FT-IR spectroscopy, Transmission Electron Microscopy, etc. Kinetics of the catalytic activities was studied using a Shimadzu GCMS-QP 5000 instrument using a closed glass reactor. All the experiments were carried out in gaseous phase using acetaldehyde as the model pollutant. Kinetic results suggest that chromium doped silica systems are good UV and visible light active photocatalysts. This is a good example for a localized photocatalytic activity. In contrast, our xerogel system shows comparatively high visible light photocatalytic activity for the titania based system, showing the importance of non-localized nature of photocatalysis. The Cobalt doped silica system shows interesting dark catalytic activity towards acetaldehyde and several other pollutants. Thus, in summary, based on the different activities we observed during our studies these materials could be successfully used to improve the quality of both indoor and outdoor air.
Keywords: Aerogel; Photocatalysis; Silicon Dioxide; Air Pollutant; Titanium Dioxide; Catalysis; Environmental Sciences (0768); Inorganic Chemistry (0488); Materials Science (0794)